A bench-stable N-trifluoroacetyl nitrene equivalent for a simple synthesis of 2-trifluoromethyl oxazoles. Issue 30 (20th July 2021) - Kobayashi, Yusuke; Masakado, Sota; Murai, Takuya; Hamada, Shohei; Furuta, Takumi; Takemoto, Yoshiji
Abstract : ortho -Nitro-substituted N -trifluoroacetyl imino-λ 3 -iodane is a bench-stable trifluoroacetyl nitrene precursor, in which intra- and intermolecular halogen bonding (XB) plays an important role. Abstract : ortho -Nitro-substituted N -trifluoroacetyl imino-λ 3 -iodane is a bench-stable trifluoroacetyl nitrene precursor, in which intra- and intermolecular halogen bonding (XB) plays an important role. Potential synthetic applications of this novel precursor were explored.